Asia in your window frame: museum displays, window curators and Dutch-Asian material culture - Grasskamp, Anna; Loeseke, Annette (World art, 2015)
This article seeks to analyse the material, architectural and conceptual framing of Asian artefacts in semi-private and public display spaces in the Netherlands. In examining the staging of ‘Buddha heads’ arranged by private ‘window curators’ in Dutch streets and exhibits presented by specialized staff members of representative institutions, the article draws attention to the use of Asian art in the staging of private stories and the grand narrative of the Dutch Golden Age. Through historical cases, recent fieldwork, a visitor study, and museum display analysis, the authors examine the presentation of Asian objects in the conspicuous semi-private settings of Dutch window frames, as well as in the public domain of the museum. The most visited museum of the country, the recently re-opened Rijksmuseum and its Asian Pavilion, provide a particularly significant case study as a ‘window of the nation’, in which Dutch culture and national identity are put on display by means of, and alongside, non-Dutch art, visual and material culture. What do the labels ‘Asian Pavilion’ and ‘Asian Art’ imply, and how can they embody a certain epistemic violence? How do visitors interpret exhibits that are mostly supplied through the private collectors of the Society of the Friends of Asian Art? Taking into consideration the viewpoints of museum visitors, museum curators, (art) historians, and post-colonially informed scholars with an Asian Studies background, the authors shed light on strategies of framing and ‘othering’ within the semi-public spaces of Dutch window frames and the public realm of the national museum.
Gesehen am 24.04.2020